Long-Baseline Oscillation Experiments as a Tool to Probe High Energy Flavor Symmetry Models - Pedro Pasquini (Advances in High Energy Physics)
We review the current status of neutrino oscillation experiments, mainly focusing on T2(H)K, NOνA, and DUNE. Their capability to probe high energy physics is found in the precision measurement of the CP phase and θ23. In general, neutrino mass models predict correlations among the mixing angles that can be used to scan and shrink their parameter space. We updated previous analysis and presented a list of models that contain such structure.